Reply to Lolli et al - Coyne, J. O. C.; Nimphius, S.; Newton, R. U.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2020)
We thank Lolli et al for their comment on our recent article "Does mathematical coupling matter to the acute to chronic workload ratio? A case study from elite sport. In their comment, Lolli et al highlighted the potential of psuedoreplication3 in our paper`s statistical analysis. We agree that we had fallen foul of this analytical pitfall and appreciate their identification of this issue. We have since reanalyzed the data using what we consider more appropriate measures for within-subject analysis to address the overall statistical concerns including psuedoreplication. Our analysis now includes examining the repeated-measures correlations (as suggested by Lolli et al) between (1) acute training load (ATL) and coupled and uncoupled chronic training load (CTL) and (2) coupled and uncoupled acute-to-chronic workload ratios (ACWR). These repeated-measures correlations between coupled ATL-CTL and uncoupled ATL-CTL have also been compared against one another with r-z transformations. The results are presented in Table 1. In addition, we extended the statistical revision to evaluate the outcome using linear mixed models (with the athlete and the time point [day] as random intercept) to determine if there are significant differences between coupled and uncoupled CTL and coupled and uncoupled ACWR. Effect sizes of these differences (marginal f2) were then calculated and interpreted as trivial (<0.02), small (0.02-0.14), medium (0.15-0.34), and large (>0.35)6 as presented in Table 2. All statistical analyses were performed using the R statistics package (https://www.r-project.org; R Foundation for Statistical Computing, Vienna, Austria), and our R script has been provided as Supplementary Material (available online). The key findings of this reanalysis suggest that there may not be a natural correlation between ATL and CTL irrespective of any coupling in the calculation of the CTL with the current real data. This is contrary to what our original article suggested. However, despite significant differences between coupled and uncoupled CTL (in all but open-skill internal and external training load [TL] as an exponentially weighted moving average), the effect sizes of these differences appear trivial (f2<0.02). There also appear to be very large to nearly perfect correlations between coupled and uncoupled ACWR. Similar to CTL, the differences between coupled and uncoupled ACWR, where significant, appear trivial. This is similar to what we reported in our original article. It is also consistent with our original interpretation that mathematical coupling had little effect on practical measures of the ACWR in this case study despite the nature of the sport, training-load calculation method, or whether internal or external load was used.